2012
DOI: 10.3324/haematol.2012.066290
|View full text |Cite
|
Sign up to set email alerts
|

Improved platelet survival after cold storage by prevention of glycoprotein Ib  clustering in lipid rafts

Abstract: The online version of this article has a Supplementary Appendix. BackgroundStoring platelets for transfusion at room temperature increases the risk of microbial infection and decreases platelet functionality, leading to out-date discard rates of up to 20%. Cold storage may be a better alternative, but this treatment leads to rapid platelet clearance after transfusion, initiated by changes in glycoprotein Ibα, the receptor for von Willebrand factor. Design and MethodsWe examined the change in glycoprotein Ibα d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Moreover, PKA activator effectively prevented apoptotic events in platelets incubated with S. aureus isolated from sepsis patients ( Figure 8, D and E). Forskolin also significantly inhibited ΔΨ m depolariza- vation of p38 MAPK and p38 MAPK-mediated cytosolic phospholipase A2, resulting in release of arachidonic acid from membrane phospholipids, which transfers 14-3-3 to the cytoplasmic domain of GPIbα (48,49). In the meantime, p38 MAPK activates ADAM17, leading to GPIbα ectodomain shedding (47), which enhances GPIbα clustering and association of 14-3-3 with the cytoplasmic domain of GPIbα (50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PKA activator effectively prevented apoptotic events in platelets incubated with S. aureus isolated from sepsis patients ( Figure 8, D and E). Forskolin also significantly inhibited ΔΨ m depolariza- vation of p38 MAPK and p38 MAPK-mediated cytosolic phospholipase A2, resulting in release of arachidonic acid from membrane phospholipids, which transfers 14-3-3 to the cytoplasmic domain of GPIbα (48,49). In the meantime, p38 MAPK activates ADAM17, leading to GPIbα ectodomain shedding (47), which enhances GPIbα clustering and association of 14-3-3 with the cytoplasmic domain of GPIbα (50).…”
Section: Discussionmentioning
confidence: 99%
“…20 In brief, 6B4-Fab fragments conjugated to either Alexa Fluor-488 or Alexa Fluor-594 (6B4-488 and 6B4-594, respectively) were incubated with fixed platelet samples under conditions in which each Fab labeled ~50% of the total number of receptors. GPIbα translocation to lipid rafts was determined by labeling GPIbα with 6B4-488 and monosialo-tetrahexosylganglioside (GM1) with Cholera toxin subunit B conjugated to Alexa Fluor-594 (CTB-594; 5 μg/mL).…”
Section: Analysis Of Gpibα Distribution By Förster Resonance Energy Tmentioning
confidence: 99%
“…18,19 During efforts to optimize the storage conditions of platelet concentrates used for transfusion, we recently demonstrated that GPIbα clusters in lipid rafts when platelets are kept at low temperature. 20 . Shear-induced clustering was reversible, not accompanied by granule release or αIIbβ3 activation and improved glycoprotein Ibα-dependent platelet interaction with von Willebrand factor.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated platelets are commonly stored at room temperature to avoid the decrease in function that can arise at lower temperatures. Consequently, isolated platelets are viable for a maximum of 5-7 days (Gitz et al 2012), making routine platelet isolation is the only option for maintaining a constant supply of platelets.…”
Section: Introductionmentioning
confidence: 99%